2005
DOI: 10.1080/0284431051003565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term use of oral smokeless tobacco on random-pattern skin flap survival in rats

Abstract: We investigated the effects of smokeless tobacco on the survival of random-pattern skin flaps in rats. Twenty rats were divided into two groups (n=10 each). In the experimental group 200 mg smokeless tobacco (Maras powder) (1 mg nicotine) was inserted intraorally once a day for seven days under general anaesthesia. It was not given to the control group, but the rats were similarly anaesthetised with ketamine. On day 8, plasma cotinine concentrations were measured. The random-pattern dorsal skin flaps measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, smokers experience a higher rate of delayed wound healing at the recipient site with higher rates of flap debridement and repeat skin grating compared with non-smokers [8]. Smokeless tobacco in the form of "Maras otu" was found to be associated with significantly higher rates of flap necrosis in a rat dorsal random skin flap model when administered daily after the flaps were raised [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smokers experience a higher rate of delayed wound healing at the recipient site with higher rates of flap debridement and repeat skin grating compared with non-smokers [8]. Smokeless tobacco in the form of "Maras otu" was found to be associated with significantly higher rates of flap necrosis in a rat dorsal random skin flap model when administered daily after the flaps were raised [13].…”
Section: Discussionmentioning
confidence: 99%
“…13 Nicotine increases platelet adhesiveness by inhibiting prostacyclin, 14 leading to thrombotic microvascular occlusion and tissue ischemia, as demonstrated by numerous studies using random-pattern skin flaps in rats. [15][16][17][18][19] Tobacco also has been shown to inhibit endothelial cell and fibroblast function, 20 nitric oxide synthase activity, 21 and vascular endothelial growth factor production 22 Further, Sorensen et al 23 found that wound inflammation and contraction, fibroblast proliferation, collagen synthesis, and vitamin-C levels were all decreased in smokers. However, use of the nicotine patch or gum was not associated with decreased wound-tissue oxygen tension, thought to be a result of the reduced levels and rate of nicotine absorption in the patch or gum compared with smoked nicotine.…”
Section: Experimental Studiesmentioning
confidence: 95%